Primary Pulmonary Artery Sarcoma Confined to the Left Pulmonary Artery - Ellery Altshuler MD; Grant Lowther MD; Michael Jantz MD (SAGE Publishing, 2021)
Primary pulmonary artery sarcomas (PPAS) are extremely rare tumors that are often mislabeled as pulmonary emboli (PE). PPAS usually involve the pulmonary trunk and are histologically classified as leiomyosarcoma, spindle cells sarcoma, fibrous histiocytoma, or undifferentiated sarcoma. Our case involved a 78-year-old man with an undifferentiated PPAS confined to the left pulmonary artery that was initially misdiagnosed as a PE. After a month-long delay in treatment in which the patient was prescribed warfarin, the correct diagnosis was made. Pulmonary artery endarterectomy and left lung pneumonectomy were performed, and he survived for 18 months before disease recurrence and death. Our case helps illustrate some of the clinical and radiographic findings that help distinguish PPAS from PE.